An analytical study of acute abdomen in established cases of pneumoperitoneum - Prabhu, E.; Lakshmibady, S. (International Surgery Journal, 2018)
Background: Pneumoperitoneum refers to the presence of air within the peritoneal cavity. The most common cause is a perforation of the abdominal viscous, a perforated ulcer, although a pneumoperitoneum may occur as a result of perforation of any part of the bowel. The exception is a perforated appendix, which seldom causes a pneumoperitoneum. The aim of present investigation was to know the various clinical features of acute abdomen in established cases of pneumoperitoneum and to study the various surgical techniques used in the management. Methods: This study is an analytical study of 103 patients admitted in emergency surgical wards. The relevant history, clinical examination, relevant investigations, and treatment were obtained by pretested proforma. Results: The symptoms such as abdominal pain, abdominal distension, fever, and vomiting were present in our study. The most common symptom was an abdominal pain in almost all cases the overall mortality in our study was 6.79% most of them is due to colonic and duodenal perforations. In most of the cases, the cause of death was diagnosed as septicemia. Conclusions: The incidence of GI Perforations can be reduced by educating the patients with appropriate medical management of peptic ulcer, tuberculosis, typhoid fever and also avoiding factors such as smoking and Alcohol.